(untitled) (Research, Society and Development, 2021)
Alembic cachaça is a beverage of great cultural and economic importance in Brazil. However, its quality is variable and difficult to control, mainly because the fermentation process occurs in open vats and is conducted by many different microorganisms which produce a great variability of chemical compounds. The use of selected yeast strains as starters has been considered an excellent alternative to the traditionally used spontaneous fermentation, since it allows the production of cachaças less subject to variation and in general, of higher quality. Still, the use of yeast strains isolated from producing areas (autóctones) would contribute for the production of beverages which carry the identity of the geographic region. In this study, we evaluated the volatile fraction of organic compounds in musts and cachaças produced by three autóctones Saccharomyces cerevisiae yeast strains. Our aim was to correlate the chemical profile of the samples with the strains to evaluate the viability of using such starters for large-scale cachaça production. More than 200 compounds belonging to seven different chemical groups were identified using solid-phase microextraction coupled to gas chromatography-mass spectrometry. The number of compounds identified in the cachaças was superior to those found in musts and those that most influenced for the differentiation of the samples were acetic and octanoic acid for musts, and ethyl decanoate and ethyl dodecanoate esters for cachaças. Multivariate analysis showed that the distillation process, as well as the fermentation microenvironment had the greatest influence on the chemical composition.